El modelo soviético en los años 1930: los viajes de María Teresa León y Rafael Alberti a Moscú - Allison Taillot (Cahiers de Civilisation Espagnole Contemporaine, 2012)
In the thirties, Spain was the scene of a deep transformation of the intellectual, who then became established as a social actor. This process coincided with the progression of communism among the members of a community of intellectuals dominated by the «Generation of ’27». In this article, we will study the relationship between these two phenomena through the analysis of the life and creative trajectories of Rafael Alberti and María Teresa León, two revolutionnary intellectuals emblematic of this period, who travelled three times to the USSR: in 1932, 1934 and 1937.